Milo Sweedler. The Dismembered Community: Bataille, Blanchot, Leiris, and the Remains of Laure. Newark: U of Delaware P, 2009. 214 pp. - Jeff Fort (Studies in 20th & 21st Century Literature, 2014)
Review of Milo Sweedler. The Dismembered Community: Bataille, Blanchot, Leiris, and the Remains of Laure. Newark: U of Delaware P, 2009. 214 pp.
Keywords: Colette Peignot; Laure; Georges Bataille; Maurice Blanchot; Michel Leiris